Angular Distribution of Damping Coefficient of Ablated Particle in Pure He, Ne, and Ar Gases. (28th September 2011) - Wang, Yinglong; Zhai, Xiaolin; Ding, Xuecheng; Hu, Ziqiang; Chu, Lizhi; Deng, Zechao; Liang, Weihua; Zhao, Yajun; Fu, Guangsheng
Abstract : To investigate the angular distribution of damping coefficient of ablated particle under various ambient gases, nanocrystalline silicon films are systemically deposited on a circular substrate by pulse laser ablation in pure He, Ne, and Ar gases, respectively. Scanning electron microscopy images and Raman and X-ray diffraction spectra indicate that the average size of Si nanoparticles decreases with the increase of the departure angle between the film and the plume, and Ne gas induces the smallest and most uniform Si nanoparticles in size among all the three gases. Further theoretical simulation demonstrates the bigger the departure angle, the smaller the damping coefficient of ablated particle, and the damping coefficient in Ne gas is largest for the same angle, implying the most effective energy transfer between Si and ambient atoms.